Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - George, T. S.; Giles, C. D.; Menezes-Blackburn, D.; Condron, L. M.; Gama-Rodrigues, A. C.; Jaisi, D.; Lang, F.; Neal, A. L.; Stutter, M. I.; Almeida, D. S.; Bol, R.; Cabugao, K. G.; et al. (Plant and soil, 2018)
Background The dynamics of phosphorus (P) in the environment is important for regulating nutrient cycles in natural and managed ecosystems and an integral part in assessing biological resilience against environmental change. Organic P (Po) compounds play key roles in biological and ecosystems function in the terrestrial environment being critical to cell function, growth and reproduction. Scope We asked a group of experts to consider the global issues associated with Po in the terrestrial environment, methodological strengths and weaknesses, benefits to be gained from understanding the Po cycle, and to set priorities for Po research. Conclusions We identified seven key opportunities for Po research including: the need for integrated, quality controlled and functionally based methodologies; assessment of stoichiometry with other elements in organic matter; understanding the dynamics of Po in natural and managed systems; the role of microorganisms in controlling Po cycles; the implications of nanoparticles in the environment and the need for better modelling and communication of the research. Each priority is discussed and a statement of intent for the Po research community is made that highlights there are key contributions to be made toward understanding biogeochemical cycles, dynamics and function of natural ecosystems and the management of agricultural systems.